H-atom site exchange in an iridium trans-dihydrogen/hydride complex, trans-[Ir(H)(?2-H2)(iPr)4(POCOP)(DMAP)]+ - Agrawal, Nisha K.; Gayathridevi, S.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Dalton Transactions, 2023)
Treatment of trans-[Ir(H)(N)(2)((iPr)4)(POCOP)(DMAP)][BAr4f] (2) with H-2 (1 bar) under ambient conditions (298 K) results in the formation of a trans-[Ir(H)(?(2)-H-2)((iPr)4)(POCOP)(DMAP)][BAr4f] (3) complex. Complex 3 exhibits H-atom site exchange between the bound H-2 and the hydride ligands which are mutually trans to one another. A plausible mechanism of this exchange involves metal-ligand cooperativity as studied by computations.

Lanthanide mimicking by magnesium for oxazolidinone synthesis - Kumar, Rohit; Mahata, Biplab; Gayathridevi, S.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Chemistry- a european journal, 2024)
In the last decade, magnesium complexes have emerged as a viable alternative to transition-metal catalysts for the hydrofunctionalization of unsaturated bonds. However, their potential for advanced catalytic reactions has not been thoroughly investigated. To address this gap, we have developed a novel magnesium amide compound (3) using a PNP framework that is both bulky and flexible. Our research demonstrates that compound 3 can effectively catalyze the synthesis of biologically significant oxazolidinone derivatives. This synthesis involves a tandem reaction of hydroalkoxylation and cyclohydroamination of isocyanate using propargyl alcohol. Furthermore, we conducted comprehensive theoretical calculations to gain insights into the reaction mechanism. It is important to note that these types of transformations have not been reported for magnesium and would significantly enhance the catalytic portfolio of the 7th most abundant element. A monomeric magnesium compound was employed as a catalyst for the cascade cyclization of propargylic alcohol and isocyanate, resulting in the formation of pharmaceutically significant oxazolidinone derivatives. This transformation, previously attributed solely to transition metals or lanthanides, signifies a noteworthy advancement.image
Keywords: catalysis; Magnesium; oxazolidinone; pincer ligand; Sustainability